Enhancing biomass hydrolysis for biofuel production through hydrodynamic modeling and reactor design. Issue 5 (13th August 2019) - Gaona, Adriana; Lawryshyn, Yuri; Saville, Bradley
Abstract: A computational fluid dynamics model was developed to represent high‐solids enzymatic hydrolysis. This model accounted for the transient and multiphase (solids‐slurry) nature of the high‐solids enzymatic hydrolysis process. The model investigated the effect of slurry viscosity, rotational speed, and two impeller configurations on the distribution of insoluble solids. Initial CFD results identified segregation of the velocity contours for the non‐Newtonian slurry, which could potentially affect the reactor performance. The multiphase, transient CFD simulations showed that the first impeller configuration delayed the distribution of solids, and compartmentalized mixing in the reactor. The second impeller configuration, meanwhile, improved solids mixing and hydrolysis, while using lower rotational speeds (and thus, energy). The second impeller configuration also expanded the size of the pseudo‐cavern between impellers, which is critical for better dispersion of the solids. The CFD trends of the second impeller configuration were experimentally verified by conducting fed‐batch, high‐solids enzymatic hydrolysis trials with pretreated lignocellulose. The experimental results showed that the second impeller configuration provided better mixing of the non‐Newtonian slurry and enhanced solids‐enzyme interactions, leading to improved glucan‐to‐glucose conversion. This work illustrates that a transient multiphase CFD model can provide valuable insights into the design and optimization of high‐solids enzymatic hydrolysis reactors. The CFD model has identified pathways to improve the distribution of solids while reducing the energy needed for mixing. The CFD model can also guide experimental and design work to scale up these reactors from the laboratory to pilot and commercial scale. Abstract : The developed transient, two‐phase CFD model predicted operational trends for the high‐solids enzymatic hydrolysis processes, leading to reduced experimental costs and increased glucan‐to‐glucose conversion.